Analisis Mengenai Tuduhan Pelanggaran HAM atas Kebocoran Data Pribadi di Indonesia - Rezieka, Kashamira (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to analyze in more depth the issue of personal data leakage that occurred in the PeduliLindungi application from the aspect of human rights. Privacy is a right that developed from the concept of human rights, namely as part of personal self-protection. This research uses qualitative methods, data collection techniques using literature study where data is taken from books, online journals, and other secondary references. The results found that the government's negligence in maintaining the security of personal data is an action that is considered a violation of human rights, because human rights are rights whose protection is mandatory and must be carried out actively by the government or state. This leak was the result of negligence or the government's absence from efforts to maintain the security of people's personal data on the PeduliLindungi application.